The elements of materia medica and therapeutics. Volume 2, Part 2 - Pereira, Jonathan, 1804-1853 (Cambridge : Cambridge University Press, 2014)
After training as an apothecary and surgeon, Jonathan Pereira (1804-53) taught materia medica for many years. His lectures at the medical school in London's Aldersgate Street were highly successful and formed the basis for the first edition of his major encyclopaedic work on medicinal substances. A pioneering text in the field of pharmacology, Pereira's work, which he subsequently updated in further editions, provided pharmacists and medical professionals with a more rigorous scientific understanding of the drugs and remedies they prescribed. After Pereira's death, medical jurist Alfred Swaine Taylor (1806-80) and physician George Owen Rees (1813-89) prepared this revised and expanded fourth edition, interspersed with instructive woodcuts. Volume 2 is divided into two parts. Part 2 (1857) contains new articles, additional illustrations and a separate index. It concludes the analysis of organic compounds, both vegetable and animal.
Originally published: London : Longman, Brown, Green, and Longmans, and Roberts, 1857.
Keywords: Materia medica; Therapeutics